Effectiveness of Messenger Plants (Peperomia Pellucida L.) and Tai Chi Exercise as Modality Therapy for Gout Sufferers: Literature review - Lutfian; Nur Rohmawati; Nila Uli Saadah (KHD-Production, 2021)
Hyperuricemia correlated with an increase in monosodium urate crystals, which was a precipitating factor for gout arthritis. In Indonesia, this disease was more common in individuals over 34 years of age. The elderly who had gout can be associated with metabolic syndrome and increase the risk of cardiovascular disease. Pharmacological therapy of gout, such as allopurinol, had a greater potential to cause side effects in patients than complementary therapy. This article aimed to determine the effectiveness of the messenger plant (Peperomia pellucida) and Tai Chi exercise in overcoming hyperuricemia. The writing method used was a literature review. Articles were obtained through search sites: Google Scholar, Science-Direct, and NCBI, and the criteria used in the search were Indonesian and English with a range of publication years 2014-2020. Eight main journals were used as references; from these journals, it was concluded that Peperomia pellucida could inhibit the formation of uric acid with xanthine oxidase activity through its quercetin-type flavonoid content, while Tai Chi exercise could increase joint flexibility and blood circulation in patients with gout. Therefore, these therapies can be used as a reference for complementary therapy for individuals with hyperuricemia to help manage uric acid levels and reduce the risk of developing gouty arthritis.